(untitled) (Fiep Bulletin - online, 2013)
The present work aims at to contemplate concerning some subjects, such as: What does to Epistemology come to be? Why to study in the master’s degree courses? And which importance for the development of the researches? This work is justified for we consider this indispensable subject so that we can understand the relationships that permeate the production informs, as well as the relationships of this with the society in a general way. Firstly we analyzed what is the epistemology and we drew an abbreviation rescues historical of the paradigms of the positivism and of the Marxism. In a second moment, we treated of the importance of the paradigms for the development of the researches. For such a challenge we based ourselves mainly in Silvio Sánchez Gamboa (2007) and Rossana Silva (1997). We know that the masters degree courses are privileged spaces for the development of the scientific research. Therefore, they are producing in potential, of scientific knowledge, what imposes the need of critical reflection on this same knowledge (SILVA, 1997). We agreed with Sánchez Gamboa (2007) when this explicit one that the approaches have relationship with options paradigmáticas and scientific, because the methods are not neutral and the researcher consciously or doesn’t choose and it applies in research. We concluded the article, pointing our understanding that that knowledge concerning the paradigms is indispensable, not just to delimit our researches, our study object, our methodology and techniques, aiding us in the scientific production, more than that, it is a posture, a world conception.